Biomass-based air water collection gel and preparation method thereof
By integrating hydroxypropyl cellulose, modified lignin and sodium alginate to form a triple network structure, the existing hygroscopic materials have been solved, and the existing hygroscopic materials are slow in kinetics and easy to disintegrate under low humidity, achieving efficient water absorption and controllable dehydration, and providing an air hydrogel material with excellent performance.
Patent Information
- Application Number
- CN202510277391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing hygroscopic materials have slow adsorption/desorption kinetics under low humidity, and the structure is easily disintegrated due to swelling stress during the cycle. The mainstream intermittent adsorption-desorption devices have lost efficiency due to operational discontinuity, and lack universal solutions to support the large-scale application of technology.
By integrating hydroxypropyl cellulose (HPC), modified lignin, and sodium alginate to form a triple network structure, the high-intensity photosensitive and temperature-sensitive double-responsive gel material is achieved, and the characteristics of absorbing water in low temperatures when there is light and heating and dehydration when there is light.
The prepared air hydrogel material has non-toxicity, high strength, high water absorption and controllable dehydration. It overcomes the shortcomings of traditional air watergel materials in terms of safety, durability and controllability, and provides an air hydrogel material with excellent performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional polymer materials, and in particular relates to a biomass-based air water-collecting gel and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Freshwater resources on Earth only account for 2.5% of the total water volume, of which less than 0.36% is directly usable liquid freshwater. Due to geographical distribution restrictions, about 30% of the land area is arid (average annual humidity RH < 20%). Although the research and development of existing adsorption-based air water collection technology is aimed at arid areas, it still faces serious bottleneck problems: First, the adsorption / desorption kinetics of most hygroscopic materials are slow at low humidity (performance decay > 50% when RH < 30%), and the structure is easily disintegrated due to swelling stress during the cycle; second, the mainstream intermittent adsorption-desorption device has efficiency loss due to discontinuous operation, and the design and manufacture of continuous integrated equipment still lacks a universal solution, which restricts the large-scale application of the technology. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a biomass-based air water-collecting gel and a preparation method thereof. The present invention integrates hydroxypropyl cellulose (HPC), modified lignin and sodium alginate to form a high-intensity photosensitive and temperature-sensitive dual-responsive gel material with a triple network structure. The gel absorbs water at low temperature in the absence of light and dehydrates at high temperature in the presence of light, thus having the characteristics of both efficient water absorption and controllable dehydration.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a method for preparing a biomass-based air-water collecting gel, comprising:
[0007] In an oxygen-free environment, N-isopropylacrylamide is added to a sodium lignin carboxylate solution, and then an initiator is added, and the temperature is raised to carry out a grafting modification reaction. After the reaction is completed, the reaction solution is collected, cooled, diluted, anhydrous ethanol is added, stirred until the solution becomes turbid, solid-liquid separation is performed, and the precipitate is collected and washed to obtain NIPAAm-sodium lignin carboxylate;
[0008] The NIPAAm-lignin sodium carboxylate, hydroxypropyl cellulose, sodium alginate and water are uniformly mixed, poured into a mold, and a calcium salt solution is sprayed on the surface to react. After the reaction is completed, freeze-drying is performed to obtain the mold.
[0009] The present invention constructs a high-strength temperature-sensitive air hydrogel material with a triple network structure by integrating hydroxypropyl cellulose, NIPAAm-lignin sodium carboxylate, and sodium alginate. The triple network structure ensures the high strength and durability of the air hydrogel; hydroxypropyl cellulose, NIPAAm-lignin sodium carboxylate, sodium alginate, and calcium chloride are all low-toxic or non-toxic, and exhibit strong water absorption performance, ensuring that the prepared air hydrogel material has good water absorption capacity, thereby avoiding the use of toxic hygroscopic substances such as lithium chloride in the air hydrogel; the use of lignin gives the air hydrogel good photothermal properties; the presence of hydroxypropyl cellulose and NIPAAm enables the air hydrogel to absorb water at low temperature (<35°C) when there is no light, and dehydrate at high temperature (>45°C) when there is light, giving the air hydrogel the characteristic of controllable dehydration. Therefore, the air hydrogel prepared by the present invention has non-toxicity, high strength, high water absorption and controllable dehydration, and is an excellent air hydrogel material.
[0010] In some embodiments, sodium lignin carboxylate is prepared using purified lignin as a raw material, and the preparation method of the purified lignin comprises:
[0011] The kraft pulp black liquor is diluted with water and filtered to obtain preliminarily purified black liquor; the black liquor is stirred and dispersed, a dilute acid solution is added to precipitate lignin, and the lignin is washed and purified to obtain purified lignin.
[0012] In some embodiments, the concentration of the kraft black liquor after dilution is 5-10% (w / v);
[0013] In some embodiments, a dilute acid solution is added to make the pH value of the black liquor 3-4 (near the isoelectric point of lignin, at which time the precipitation amount is the largest).
[0014] In some embodiments, the preparation method of sodium lignin carboxylate includes: adding alkali to make the purified lignin alkaline, adding chloroacetic acid, and heating to carry out a grafting reaction; after the reaction is completed, cooling and diluting the reaction solution, adjusting the pH value, adding anhydrous ethanol, stirring until the solution is turbid, separating the solid and the liquid, and collecting the precipitate; washing the precipitate to obtain sodium lignin carboxylate.
[0015] In some embodiments, alkali is added to make the pH value of the purified lignin 12 to 13;
[0016] In some embodiments, the mass ratio of lignin to chloroacetic acid is 1:2-1:4;
[0017] In some embodiments, the grafting reaction temperature is 60-70°C and the reaction time is 4-6 hours;
[0018] In some embodiments, after the grafting reaction is completed, the pH value of the reaction solution is adjusted to 3-4 (using dilute acid); the volume ratio of the reaction solution to anhydrous ethanol is 1:0.5-1:2.
[0019] In some embodiments, the ratio of sodium lignin carboxylate to N-isopropylacrylamide is 1:3-1:5;
[0020] In some embodiments, the initiator is ammonium persulfate;
[0021] In some embodiments, the amount of the initiator is 0.5-2.5 wt % of the total mass of sodium lignin carboxylate and N-isopropylacrylamide.
[0022] In some embodiments, the volume ratio of the reaction solution to anhydrous ethanol is 1:0.5-1:2.
[0023] In some embodiments, the mass ratio of the NIPAAm-lignin carboxylate sodium, hydroxypropyl cellulose, and sodium alginate is 4-9: 1-3, 2-6;
[0024] In some embodiments, the concentration of the calcium salt solution is 3-6 wt %.
[0025] More specifically, they include:
[0026] (1) The kraft pulp black liquor is diluted with deionized water and filtered to obtain the preliminarily purified black liquor. The black liquor is stirred and dispersed, and a certain amount of dilute acid solution is added dropwise to the black liquor to precipitate lignin, and the lignin is washed and purified to obtain purified lignin.
[0027] (2) The purified lignin is adjusted to alkalinity with sodium hydroxide, chloroacetic acid is added, and the temperature is increased to carry out the grafting reaction. After the reaction is completed, the reaction solution is cooled and diluted, the pH value is adjusted, anhydrous ethanol is added, and the solution is stirred until turbid, and centrifuged to precipitate. The precipitate is washed by centrifugation with a mixture of ethanol and water for multiple times to obtain pure sodium lignin carboxylate.
[0028] (3) After diluting the sodium lignin carboxylate, heat and stir until it is completely dissolved. Introduce nitrogen to create an oxygen-free environment, then add N-isopropylacrylamide NIPAAm and stir until it is completely dissolved. Add APS solution dropwise to activate the reaction system, and heat to carry out grafting modification reaction. After the reaction is completed, cool and dilute the reaction solution, add anhydrous ethanol, stir until the solution is turbid, and centrifuge to precipitate. Wash the precipitate with a mixture of ethanol and water by centrifugation several times to obtain pure NIPAAm-sodium lignin carboxylate.
[0029] (4) After the NIPAAm-lignin carboxylate sodium, hydroxypropyl cellulose and sodium alginate are fully mixed, they are poured into a specific mold for molding, and calcium chloride solution is sprayed on the surface. After stabilization for a period of time, they are freeze-dried into an air-collecting hydrogel material.
[0030] The second aspect of the present invention provides a biomass-based air water-collecting gel prepared by the above method.
[0031] The third aspect of the present invention provides the use of the above-mentioned biomass-based air water-collecting gel in the preparation of a water collector.
[0032] Beneficial Effects of the Invention
[0033] (1) Structural innovation and mechanical performance improvement: By innovatively integrating hydroxypropyl cellulose, NIPAAm-lignin carboxylate sodium and sodium alginate, a triple network structure was successfully constructed, significantly improving the mechanical strength and durability of the air-collecting gel material. This unique structural design enables the material to maintain good structural integrity during long-term use.
[0034] (2) Environmental friendliness and safety: The main components of this material, including hydroxypropyl cellulose, NIPAAm-lignin sodium carboxylate, sodium alginate and calcium chloride, are low-toxic, non-toxic and have strong water absorption properties, effectively avoiding the use of toxic hygroscopic substances such as lithium chloride in traditional air water collection materials, greatly improving the environmental friendliness and safety of the material.
[0035] (3) Photothermal properties and intelligent regulation: By introducing lignin components, the material is endowed with good photothermal conversion properties. Combined with the temperature response characteristics of hydroxypropyl cellulose and NIPAAm, the material can efficiently absorb water under no light conditions (<35°C) and achieve controllable dehydration under light conditions (>45°C), realizing intelligent regulation of the water collection process.
[0036] (4) Excellent comprehensive performance: The air hydrogel material prepared by the present invention combines non-toxicity, high strength, high water absorption and controllable dehydration, overcoming the shortcomings of traditional air hydrogel materials in terms of safety, durability and controllability, and is an air hydrogel material with excellent performance.
[0037] Through the above innovative design, the present invention not only solves the technical bottleneck of traditional air water collection materials, but also provides a new type of efficient, safe and reliable material solution for the field of air water collection, which has significant technical progress and practical application value. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0039] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0040] In the following examples, the kraft pulp black liquor was taken from a hardwood kraft pulp production line of a factory in Shandong.
[0041] Example 1
[0042] (1) 8% kraft pulp black liquor is filtered through a 0.45 μm microporous filter membrane, the filtrate is collected and continuously stirred, and 5% dilute hydrochloric acid is added dropwise until the pH value of the black liquor drops to about 3.5. The filtrate is filtered through a 0.45 μm microporous filter membrane and washed with deionized water to obtain pure lignin particles.
[0043] (2) Take 5g (absolute dry weight) of lignin particles, add them to 50ml of sodium hydroxide solution with a pH of 12-13, add 15g of chloroacetic acid, heat to 65°C in a water bath, and continue stirring to react for 5 hours. After the reaction is completed and cooled, add 150ml of deionized water and adjust the pH to 3-4 with dilute hydrochloric acid, add 200ml of ethanol, stir until the solution is turbid, and centrifuge to obtain a modified lignin precipitate. Wash the precipitate three times with a 70% ethanol aqueous solution to obtain pure sodium lignin carboxylate.
[0044] (3) Disperse 5 g (absolute dry weight) of sodium lignin carboxylate in 400 ml of deionized water, stir at 60°C until completely dissolved, and then introduce nitrogen for 30 minutes to continuously bubble out oxygen in the system. Under nitrogen protection, add 20 g of NIPAAm and stir until completely dissolved. Then dissolve 0.25 g of APS in 5 ml of deionized water and add dropwise to the reaction system within 10 minutes. Heat the reaction system to 70°C and react at a constant temperature for 8 hours. After the reaction is completed, wait for the system to cool, add 400 ml of ethanol and stir until the solution becomes turbid, and then centrifuge to obtain a modified lignin precipitate. Finally, the precipitate is centrifuged and washed three times with a 70% ethanol aqueous solution to obtain pure NIPAAm-sodium lignin carboxylate.
[0045] (4) 6 g (absolute dry weight) of NIPAAm-lignin sodium carboxylate, 2.5 g of hydroxypropyl cellulose, and 4 g of sodium alginate were mixed, and deionized water was added to make the total weight 100 g. After stirring and mixing, 5 ml of 5% calcium chloride solution was evenly sprayed on the surface. After standing and stabilizing for 2 h, the mixture was freeze-dried to form an air-collecting gel.
[0046] The film-like air water-collecting gel with a thickness of about 0.4 cm prepared in this example can collect 19.75 g (158%) of water per hour at a humidity of 30%. Under direct sunlight at noon in autumn, 17.76 g of water can be desorbed and collected within 30 minutes.
[0047] Example 2
[0048] (1) 8% kraft pulp black liquor is filtered through a 0.45 μm microporous filter membrane, the filtrate is collected and continuously stirred, and 5% dilute hydrochloric acid is added dropwise until the pH value of the black liquor drops to about 3.5. The filtrate is filtered through a 0.45 μm microporous filter membrane and washed with deionized water to obtain pure lignin particles.
[0049] (2) Take 5g (absolute dry weight) of lignin particles, add to 50ml sodium hydroxide solution with pH 12-13, add 15g chloroacetic acid, heat to 60°C in a water bath, and continue stirring to react for 6 hours. After the reaction is completed and cooled, add 150ml of deionized water and adjust the pH to 3-4 with dilute hydrochloric acid, add 200ml of ethanol, stir until the solution is turbid, and centrifuge to obtain a modified lignin precipitate. Wash the precipitate three times with a 70% ethanol aqueous solution to obtain pure sodium lignin carboxylate.
[0050] (3) Disperse 5 g (absolute dry weight) of sodium lignin carboxylate in 400 ml of deionized water, stir at 60°C until completely dissolved, and then introduce nitrogen for 30 minutes to continuously bubble out oxygen in the system. Under nitrogen protection, add 20 g of NIPAAm and stir until completely dissolved. Then dissolve 0.25 g of APS in 5 ml of deionized water and add dropwise to the reaction system within 10 minutes. Heat the reaction system to 70°C and react at a constant temperature for 8 hours. After the reaction is completed, wait for the system to cool, add 400 ml of ethanol and stir until the solution becomes turbid, and then centrifuge to obtain a modified lignin precipitate. Finally, the precipitate is centrifuged and washed three times with a 70% ethanol aqueous solution to obtain pure NIPAAm-sodium lignin carboxylate.
[0051] (4) 4 g (absolute dry weight) of NIPAAm-lignin sodium carboxylate, 2.5 g of hydroxypropyl cellulose, and 4 g of sodium alginate were mixed, and deionized water was added to make the total weight 100 g. After stirring and mixing, 5 ml of 5% calcium chloride solution was evenly sprayed on the surface. After standing and stabilizing for 2 h, the mixture was freeze-dried to form an air-collecting gel.
[0052] The film-like air water-collecting gel with a thickness of about 0.4 cm prepared in this example can collect a maximum water amount of 16.5 g (143%) per hour in an atmospheric environment with a humidity of 30%. Under direct sunlight at noon in autumn, 14.6 g of water can be desorbed and collected within 30 minutes.
[0053] Example 3
[0054] (1) 8% kraft pulp black liquor is filtered through a 0.45 μm microporous filter membrane, the filtrate is collected and continuously stirred, and 5% dilute hydrochloric acid is added dropwise until the pH value of the black liquor drops to about 3.5. The filtrate is filtered through a 0.45 μm microporous filter membrane and washed with deionized water to obtain pure lignin particles.
[0055] (2) Take 5g (absolute dry weight) of lignin particles, add them to 50ml of sodium hydroxide solution with a pH of 12-13, add 15g of chloroacetic acid, heat to 70°C in a water bath, and continue stirring to react for 4 hours. After the reaction is completed and cooled, add 150ml of deionized water and adjust the pH to 3-4 with dilute hydrochloric acid, add 200ml of ethanol, stir until the solution is turbid, and centrifuge to obtain a modified lignin precipitate. Wash the precipitate three times with a 70% ethanol aqueous solution to obtain pure sodium lignin carboxylate.
[0056] (3) Disperse 5 g (absolute dry weight) of sodium lignin carboxylate in 400 ml of deionized water, stir at 60°C until completely dissolved, and then introduce nitrogen for 30 minutes to continuously bubble out oxygen in the system. Under nitrogen protection, add 20 g of NIPAAm and stir until completely dissolved. Then dissolve 0.25 g of APS in 5 ml of deionized water and add dropwise to the reaction system within 10 minutes. Heat the reaction system to 70°C and react at a constant temperature for 8 hours. After the reaction is completed, wait for the system to cool, add 400 ml of ethanol and stir until the solution becomes turbid, and then centrifuge to obtain a modified lignin precipitate. Finally, the precipitate is centrifuged and washed three times with a 70% ethanol aqueous solution to obtain pure NIPAAm-sodium lignin carboxylate.
[0057] (4) 9 g (absolute dry weight) of NIPAAm-lignin sodium carboxylate, 2.5 g of hydroxypropyl cellulose, and 4 g of sodium alginate were mixed, and deionized water was added to a total weight of 100 g. After stirring and mixing, 5 ml of a 5% calcium chloride solution was evenly sprayed on the surface. After standing and stabilizing for 2 h, the mixture was freeze-dried to form an air-collecting gel.
[0058] The film-like air water-collecting gel with a thickness of about 0.4 cm prepared in this example can collect 21.3 g (1.52%) of water per hour at a humidity of 30%. Under direct sunlight at noon in autumn, 20.21 g of water can be desorbed and collected within 30 minutes.
[0059] Comparative Example 1
[0060] The difference from Example 1 is that in step (4), hydroxypropyl cellulose is not added.
[0061] The air water collection gel prepared in this embodiment has poor strength and is not suitable for air water collection and water desorption.
[0062] Comparative Example 2
[0063] The difference from Example 2 is that in step (4), NIPAAm-sodium lignin carboxylate is not added.
[0064] The air-water-collecting gel prepared in this example can collect 3.05 g (29.9%) of water per hour at a humidity of 30%. Under direct sunlight at noon in autumn, 1.72 g of water can be collected within 30 minutes.
[0065] Comparative Example 3
[0066] The difference from Example 2 is that in step (4), sodium lignin carboxylate is used instead of NIPAAm-sodium lignin carboxylate.
[0067] The air-water-collecting gel prepared in this example has a maximum water collection capacity of 14.62 g (131%) per hour in an atmospheric environment with a humidity of 30%. Under direct sunlight at noon in autumn, 7.25 g of water can be collected within 30 minutes, and the cohesive strength is obviously poor and cannot be reused multiple times.
[0068] Comparative Example 4
[0069] The difference from Example 2 is that steps (1) and (2) are omitted, and in step (3), sodium carboxylate is used instead of lignin sodium carboxylate to prepare NIPAAm-sodium carboxylate.
[0070] The air-water-collecting gel prepared in this example can collect 2.8 g (23.3%) of water per hour at a humidity of 30%. Under direct sunlight at noon in autumn, 1.23 g of water can be collected within 30 minutes.
[0071] From the comparison between Example 2 and Comparative Example 2, it can be seen that the addition of NIPAAm-sodium lignin carboxylate significantly improves the water absorption capacity and controllable dehydration capacity of the air water-collecting gel.
[0072] From the comparison between Example 2 and Comparative Examples 3 and 4, it can be seen that the water absorption and controllable dehydration capacity of the air-collecting gel are significantly reduced after the NIPAAm or lignin unit is missing.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a biomass-based air water-collecting gel, characterized in that: include: In an oxygen-free environment, N-isopropylacrylamide is added to a sodium lignin carboxylate solution, and then an initiator is added, and the temperature is raised to carry out a grafting modification reaction. After the reaction is completed, the reaction solution is collected, cooled, diluted, anhydrous ethanol is added, stirred until the solution becomes turbid, solid-liquid separation is performed, and the precipitate is collected and washed to obtain NIPAAm-sodium lignin carboxylate; The NIPAAm-lignin sodium carboxylate, hydroxypropyl cellulose and sodium alginate are uniformly mixed, poured into a mold, and a calcium salt solution is sprayed on the surface to react. After the reaction is completed, freeze-drying is performed to obtain the product.
2. The method for preparing the biomass-based air water-collecting gel according to claim 1, characterized in that: Sodium lignin carboxylate is prepared using purified lignin as a raw material. The preparation method of the purified lignin comprises: The kraft pulp black liquor is diluted with water and filtered to obtain preliminarily purified black liquor; the black liquor is stirred and dispersed, a dilute acid solution is added to precipitate lignin, and the lignin is washed and purified to obtain purified lignin.
3. The method for preparing the biomass-based air water-collecting gel according to claim 2, characterized in that: The concentration of the kraft black liquor after dilution is 5-10% (w / v); Alternatively, dilute acid solution is added to adjust the pH value of the black liquor to 3-4.
4. The method for preparing the biomass-based air water-collecting gel according to claim 1, characterized in that: The preparation method of sodium lignin carboxylate comprises: adding alkali to make the purified lignin alkaline, adding chloroacetic acid, and heating to carry out grafting reaction; after the reaction is completed, cooling and diluting the reaction solution, adjusting the pH value, adding anhydrous ethanol, stirring until the solution is turbid, separating the solid from the liquid, and collecting the precipitate; washing the precipitate to obtain sodium lignin carboxylate.
5. The method for preparing the biomass-based air water-collecting gel according to claim 4, characterized in that: adding alkali to make the pH value of the purified lignin 12 to 13; Or, the mass ratio of lignin to chloroacetic acid is 1:2-1:4; Or, the grafting reaction temperature is 60-70°C, and the reaction time is 4-6 hours; Alternatively, after the grafting reaction is completed, the pH value of the reaction solution is adjusted to 3-4; the volume ratio of the reaction solution to anhydrous ethanol is 1:0.5-1:
2.
6. The method for preparing the biomass-based air water-collecting gel according to claim 1, characterized in that: The dosage ratio of the sodium lignin carboxylate to N-isopropylacrylamide is 1:3-1:5; Or, the initiator is ammonium persulfate; Alternatively, the amount of the initiator is 0.5-2.5 wt % of the total mass of sodium lignin carboxylate and N-isopropylacrylamide.
7. The method for preparing the biomass-based air water-collecting gel according to claim 1, characterized in that: The volume ratio of the reaction solution to anhydrous ethanol is 1:0.5-1:
2.
8. The method for preparing the biomass-based air water-collecting gel according to claim 1, characterized in that: The mass ratio of the NIPAAm-lignin sodium carboxylate, hydroxypropyl cellulose and sodium alginate is 4-9: 1-3, 2-6; Alternatively, the concentration of the calcium salt solution is 3-6 wt %.
9. The biomass-based air water-collecting gel prepared by the method according to any one of claims 1 to 8.
10. Use of the biomass-based air water-collecting gel according to claim 9 in preparing a water collector.
Citation Information
Patent Citations
Preparation method and application of hemicellulose-based composite temperature-sensitive gel
CN110028624A
Dual-network hydrogel as well as preparation method and application thereof
CN117801321A
Thermogelling graft copolymer and method of preparation thereof
US20170210840A1
Molecularly confined hydration in thermoresponsive hydrogels for efficient atmospheric water harvesting
WO2025038178A2
Cited By
Biomass fertilizer for improving soil environment and preparation method thereof
CN121159342A